1975
DOI: 10.1128/iai.12.5.1051-1057.1975
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro stimulation of mouse spleen leukocytes by BL-20803, a low-molecular-weight interferon inducer

Abstract: BL-20803, a low-molecular-weight compound, although able to elicit circulating interferon in the mouse, failed to protect cultured cell lines in vitro from infection by interferon-sensitive viruses. Of the tissues analyzed for interferon content after oral administration of the drug to mice, spleen and lung contained the largest amounts of the virus inhibitor. Spleen cells from such dosed animals when isolated into in vitro cultures elaborated small amounts of interferon into the culture medium. The time seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
1977
1977

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…3. Mice DISCUSSION Most low-molecular-weight inducers of interferon unrelated to mercaptoalkylamines probably stimulate specialized cell types within the body, since they induce interferon formation in the whole animal but usually do not stimulate nonlymphoid cells in cultures (12,19,20). The current studies demonstrate that the aminothiols are different in that they stimulate both mouse and human cultures, as do high-molecular-weight polynucleotides and viruses (10).…”
Section: Emovalofmentioning
confidence: 60%
See 1 more Smart Citation
“…3. Mice DISCUSSION Most low-molecular-weight inducers of interferon unrelated to mercaptoalkylamines probably stimulate specialized cell types within the body, since they induce interferon formation in the whole animal but usually do not stimulate nonlymphoid cells in cultures (12,19,20). The current studies demonstrate that the aminothiols are different in that they stimulate both mouse and human cultures, as do high-molecular-weight polynucleotides and viruses (10).…”
Section: Emovalofmentioning
confidence: 60%
“…Because of their possible use as radioprotective drugs, the pharmacology and toxicology of mercaptoalkylamines and thiophosphate derivatives have been studied in animals and man, and some have been shown to be relatively safe. A property of low-molecular-weight interferon inducers such as tilorone (12), BL-20803 (19), and MA-56 (20) is that they may be taken orally and still induce systemic interferon. Such a study is indicated for aminothiols.…”
Section: Emovalofmentioning
confidence: 99%